A literatura na aquisição de línguas estrangeiras: uma reflexão à luz da linguística e da psicanálise. - Martins, Dayse Limeira (2022)
We propose to carry out theoretical research in the light of freud lacanian psychoanalysis and saussurean jakobsonian linguistics. In this sense, we propose that the inclusion of literature as a didactic resource in the teaching learning process of a forei gn language can produce, can affect positively this affective/subjective dimension, since literature allows a release of affections and transformation of the subject., but also because it is related to the art of telling and listening to stories, it allows a sound experience with other languages, promoting the rupture of barriers that imprison the subject to his mother language, minimizing his resistance in relation to the new language. However, it is also important to say that, although literature can mini mize difficulties in learning a foreign language, they will always exist, as the acquisition of this new language occurs in a particular way for each subject. Thus, the general objective of this research is to discuss the insertion of literature as a didac tic resource in the teaching and learning of foreign languages through storytelling, considering the subjective effects of this learning. And as specific objectives: to relate the acquisition of the mother language to the foreign language, to discuss the subjective effects of learning a foreign language according to the specific bond that the subject maintains with his/her mother language and to reflect on the subjective incidences of learning a language in the light of the clinical cases of Anna O. and W olfson, as well as the biographies of Elias Canetti and Aharon Appelfeld. The discussions undertaken reveal the subjective effects of a language and literature as an important didactic resource because it allows a release of affections and transformation of the subject, as well as through sound games it can contribute to the entry into the acquisition of a foreign language.